Dacron velour arteriovenous fistula for hemodialysis access. - Lindenauer, S M (1981)
Dacron velour arteriovenous fistulas were created in the necks of 12 dogs. Sham dialysis was performed three times per week for one month in six animals, and for six months in an additional six animals. One prosthesis became infected, and perigraft bleeding occurred twice. There were no false aneurysms, and all prostheses remained patent. Dacron velour appears to be a satisfactory prosthetic material for use as an arteriovenous fistula for chronic hemodialysis access. The enhanced fibrous tissue adherence of Dacron velour may account for the few complications encountered.